Correction: Comprehensive target capture/next-generation sequencing as a second-tier diagnostic approach for congenital muscular dystrophy in Taiwan. - Wen-Chen Liang; Xia Tian; Chung-Yee Yuo; Wan-Zi Chen; Tsu-Min Kan; Yi-Ning Su; Ichizo Nishino; Lee-Jun C Wong; Yuh-Jyh Jong (PLoS ONE, 2017)
[This corrects the article DOI: 10.1371/journal.pone.0170517.].